ANALISIS KONSEPSI ASAS FIRST TO FILE DALAM PEMBATALAN MEREK TERDAFTAR (CONTOH KASUS: PUTUSAN KASASI MAHKAMAH AGUNG NO. 999 K/PDT.SUS-HKI/2019 DAN PUTUSAN PENGADILAN NEGERI NO. 15/PDT.SUS-MEREK/2015/PN.NIAGA.JKT.PST) - Michelle Nathania; Ariawan Gunadi (Fakultas Hukum Universitas Tarumanagara, 2020)
With the development of the industry, the use of advertising to introduce products has also grown. Trademarks are intellectual property rights that are used to identify goods and services of a company. By using the brand, the entrepreneurs can protect their brand. Trademark law is regulated in Law Number 20 of 2016 concerning Trademarks and Geographical Indications. In the registration of a mark, it is known as the first to file principle. In this system, registrants are required to register in order for their trademarks to be protected. This system confirms that the person who registers the mark for the first time is the one who has the right to the mark. In the first to file principle, there are often differences in interpretation where judges in deciding cases have different interpretations. The first to file principle also often collides with well-known brands. This study aims to determine the extent of the interpretation of the first to file principle in the trademark registration system in Indonesia and to determine the suitability of judges' judgments in relation to the Trademark Law No. 20 of 2016 concerning trademarks and geographical indications.